Fast and Facile Microwave Synthesis of Cubic CuFe2O4 Nanoparticles for Electrochemical CO2 Reduction. Issue 4 (25th January 2023) - Zander, Judith; Weiss, Morten; Marschall, Roland
Abstract : Nanoparticles of cubic CuFe2 O4 are obtained in a fast microwave‐assisted hydrothermal synthesis. By adjusting the pH value and solvent ratio (ethylene glycol to water), phase purity and high crystallinity is achieved at very short reaction times of 1 min, or low temperatures of 120 °C, without the need for subsequent heat treatment steps. The influence of the synthesis time or temperature on material properties and performance in electrochemical CO2 reduction to CO are investigated. While particle size and crystallinity are not changed significantly with longer synthesis times at 175 °C, prolonged heating results in a decrease of the degree of inversion, which leads to a decrease in the CO2 reduction ability. The best performance is observed for CuFe2 O4 with an intermediate degree of inversion of approx. 0.75, together with the largest crystallite size and micro‐strain, as revealed by Rietveld refinement. For CuFe2 O4 synthesized under these conditions, a CO evolution rate of 0.2 μmol h −1  g −1 is obtained at a Faradaic efficiency of 20%. The CO to H2 ratio is 1:3, which makes it a promising candidate for a sustainable production of syngas. Abstract : Nanoparticles of cubic CuFe2 O4 are obtained in a fast microwave‐assisted aqueous synthesis. Phase‐pure nanoparticles with controllable size between 10 and 20 nm can be achieved already in one minute. Besides investigating the varying synthesis parameters thoroughly, the obtained nanoparticles are applied in electrochemical CO2 reduction, solely generating CO and H2 .